A study of a successful experienced elite handball coach's cognitive processes in competition situations - Debanne, T.; Fontayne, P. (International Journal of Sports Science and Coaching, 2009)
This study explores the cognitive management of a successful experienced elite handball coach during a competition. A coach's activity was examined based on a "single case" by analyzing the content of two types of interviews (semi-structured, stimulated recall) through deductive, then inductive approaches. Results showed: (a) in the planning phase, game plans intended for the competition were elaborated from situations that had long been mastered during training sessions: and (b) in the interactive phase on offense, the coach carried out adjustments through his players (especially the playmaker); on defense, changes were made using a basic knowledge of game systems. The coach's activity was organized into six prioritized tasks relating to: i) players' physical engagement; ii) management of collective duels; iii) management of individual duels; iv) refereeing; v) players' energy management; and vi) technical-tactical instruction to the substitutes. Cognition was principally distributed by interacting with the team's playmaker.